Determination of appropriate areas in terms of bio comfort by using summer temperature index with the help of GIS throughout Ordu province - Cetin, Mehmet; Alrabiti, Osama B Muragaa (Journal of Design for Resilience in Architecture & Planning, 2022)
Threshold values for climate elements have been determined and some indices have been developed, especially with studies on human comfort. It is a fact that the feeling of comfort is subjective and there are different psychological and physical factors affecting this feeling. However, the presentation of threshold values and indices is very interesting in determining the current state of the climate conditions of the environment in terms of average and optimal values and the extent of deviation from the most appropriate values. The values of the climate elements that need to be looked at in order to provide bioclimatic comfort; it as a combination of 21-27.5 °C temperature, 30-65% relative humidity and wind speed up to 5 m/s in open area. These values have been used in many bioclimatic assessments. In addition to being an effective factor in almost every aspect of people's lives, bio comfort is also important in the periods when tourism activities are carried out. Thus, it is extremely important to determine the regions that are not suitable for bio comfort in the season of tourism in the regions that tourism activities are carried out. The aim of this research is to determine the suitable and unsuitable areas in terms of bio comfort in summer by using New Summer Index throughout Ordu province via GIS. As a conclusion, it has been determined that the area covering approximately 57.62% of the southern part of the province is cold, and the most comfortable part of the province is the part covering approximately 11.12% of the province and located by the sea in the north of the province.
Keywords: Building construction; Architecture; tourism; Ordu; ordu; summer temprature index; NA1-9428; bio comfort; TH1-9745; 13. Climate action; 11. Sustainability